Investigation of single surface acoustic wave sources - Hesjedal, T; Behme, G (IEE, 2000)
The first experimental investigation of a single gap surface acoustic wave (SAW) source on GaAs is reported. Using scanning acoustic force microscopy, SAWs are measured with sub-wavelength resolution and an unmatched sensitivity. Phase and amplitude images reveal the radiation characteristics of a single gap source, allowing for a deeper insight into SAW device operation and future design improvements.